2018
DOI: 10.3897/phytokeys.113.30027
|View full text |Cite
|
Sign up to set email alerts
|

Medinilla theresae (Melastomataceae), a new species from ultramafic soils in the Philippines

Abstract: A new species, Medinillatheresae Fernando, from ultramafic soils on Dinagat and Mindanao Islands, Philippines is described and illustrated. The species is characterized by its terrestrial erect habit, non-setose nodes, 3-plinerved, lanceolate and coriaceous leaves arranged in whorls, cauline or axillary and pendulous inflorescences, rounded flower buds, 4-merous flowers, and straight anthers. It is compared with other similar species in the Medinillapendula Merr. complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…It is considered part of the Greater Mindanoa biogeographic region (Ong, Afuang, & Rosell-Ambol, 2002) and marks the northernmost landmass in the Eastern Mindanoa Biodiversity Corridor (Ibañez & Salvador, 2008). This island boasts a high level of floral and faunal endemism (Ambal et al, 2012;Heaney & Rabor, 1982), with new plant species continually being described (Fernando, Quakenbush, Lillo, & Ong, 2018;Fernando & Wilson, 2021;Maglangit et al, 2021). In a study of plant diversity on Dinagat Island, Lillo et al (2019) reported 432 native species from 87 families and 203 genera from six forest habitat types and with at least 40 island-endemic taxa.…”
Section: Taxonomymentioning
confidence: 99%
“…It is considered part of the Greater Mindanoa biogeographic region (Ong, Afuang, & Rosell-Ambol, 2002) and marks the northernmost landmass in the Eastern Mindanoa Biodiversity Corridor (Ibañez & Salvador, 2008). This island boasts a high level of floral and faunal endemism (Ambal et al, 2012;Heaney & Rabor, 1982), with new plant species continually being described (Fernando, Quakenbush, Lillo, & Ong, 2018;Fernando & Wilson, 2021;Maglangit et al, 2021). In a study of plant diversity on Dinagat Island, Lillo et al (2019) reported 432 native species from 87 families and 203 genera from six forest habitat types and with at least 40 island-endemic taxa.…”
Section: Taxonomymentioning
confidence: 99%
“…Medinilla memiliki distribusi dari Afrika tropis, Madagaskar, India, Sri Lanka, Myanmar, China bagian selatan, Taiwan, Indochina, Thailand, Peninsular Malaysia, Indonesia, Filipina, New Guinea, Australia bagian utara, Mikronesia, Solomons, Vanuatu, Fiji, dan Samoa (Fernando & Balete, 2013;Regalado, 1990). Genus ini diperkirakan berjumlah 381 (Bodegom & Veldkamp, 2001;Fernando et al, 2018;Kartonegoro & Veldkamp, 2017;Lin & Rubite, 2020) dengan pusat keragaman tertinggi ada di Madagaskar, Filipina dan New Guinea (Bodegom & Veldkamp, 2001;Regalado, 1995). Untuk Indonesia belum ada data tentang jumlah keragaman medinilla.…”
Section: Pendahuluanunclassified
“…Medinilla memiliki distribusi dari Afrika tropis, Madagaskar, India, Sri Lanka, Myanmar, China bagian selatan, Taiwan, Indochina, Thailand, Peninsular Malaysia, Indonesia, Filipina, New Guinea, Australia bagian utara, Mikronesia, Solomons, Vanuatu, Fiji, dan Samoa (Fernando & Balete, 2013;Regalado, 1990). Genus ini diperkirakan berjumlah 381 (Bodegom & Veldkamp, 2001;Fernando et al, 2018;Kartonegoro & Veldkamp, 2017;Lin & Rubite, 2020) dengan pusat keragaman tertinggi ada di Madagaskar, Filipina dan New Guinea (Bodegom & Veldkamp, 2001;Regalado, 1995). Untuk Indonesia belum ada data tentang jumlah keragaman medinilla.…”
Section: Pendahuluanunclassified